THU0155 Sensitivity to Change of the Ultrasound Disease Activity Score. (23rd January 2014) - Radunovic, G.; Prodanovic, S.; Simic Pasalic, K.; Milic, V.; Damjanov, N.
Abstract : Background: We have investigated construct validity and reliability of the Ultrasound Disease Activity Score (USDAS) compared with DAS28 in assessing joint inflammation and in prediction of structural damage in patients with rheumatoid arthritis (RA). Our results showed strong correlation between USDAS and standard assessment of disease activity: DAS28, ESR and CRP levels. Moreover, USDAS correlated with X-ray, MRI and US parameters and rates of joint damage, and better anticipated future joint damage than standard DAS28 (1 ). Objectives: To evaluate the sensitivity to change of USDAS and the predictive value of USDAS in measuring disease activity in patients with established RA. Methods: 64 patients with active RA were prospectively recruited and followed up during the 6 months of treatment. The mean age of patients (S.D.) was 55.8 (11.6) years (range 27-82 years) and the mean disease duration was 60.3 (61.6) months (range 4-360 months). The patients underwent clinical and laboratory assessment, along with blinded power Doppler US (PDUS) and grey-scale (GS) US (GSUS) examination at baseline, 3 and 6 months. A PDUS examination of 22 joints and GSUS examination for effusion/hypertrophy (E/H) of 28 joints were performed by two independent examiners, blinded to clinical findings. PDUS and GSUS examinations were based on standard EULAR reference scans, using US workstation Logiq9 (GE Medical Systems) with a M12L Matrix Array 5-13 MHz linear probe. E/H was assessed as absent or present, and PD signal was semi-quantitatively graded from 0 to 3. USDAS was designed by replacing the number of tender joints in DAS28 with PD semi-quantitative score of the 22 joints (wrists, MCPs, and MTPs) and by replacing the number of swollen joints with GSUS E/H28 score (same joints as in DAS28). The formula for USDAS was: USDAS=0.56×(PD22)+0.28×(E/H28)+0.70×ln(ESR)+0.014×(GH). The sensitivities to change of USDAS and DAS28 were assessed by calculating the Standardized Response Means (SRMs) in a subgroup of patients with positive ACR20 response at 3 and 6 months of treatment. The predictive values of USDAS and DAS28 at the end, as well as USDAS and DAS28 baseline-end differences in disease activity outcome were estimated by ROC curves with ACR20 as criterion of the favorable response. Results: SRMs in patients with positive ACR20 response at 3 and 6 months of treatment are shown in following table: Area under the ROC curves for USDAS and DAS28 end values and baseline-end differences at 6 months are shown in the second table: Conclusions: Sensitivity to change of USDAS was comparable to sensitivity to change of DAS28. USDAS better predicted favorable ACR20 response after 6 months of treatment than DAS28. References: Damjanov N, Radunovic G, Prodanovic S et al. Construct validity and reliability of ultrasound disease activity score in assessing joint inflammation in RA: comparison with DAS28. Rheumatology 2012;51:120-8. Disclosure of Interest: None Declared